The Impact of Palm Oil Plantation Exploitation on the Environment in Sumatra : Analysis of Legal Violations - Euis Maesaroh; Intan Sukmawati; Kanisa Sabila; Sitta Khairunnisa (International Journal of Law and Society, 2026)
Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia guarantees the right of every person to live in a good and healthy environment, while Article 33 paragraph (4) of the 1945 Constitution of the Republic of Indonesia affirms the principle of sustainable and environmentally friendly development as the basis for natural resource management. These constitutional norms are implemented through Law No. 32 of 2009 concerning Environmental Protection and Management, which requires every business activity to prevent any pollution and/or environmental damage. In addition, through Law Number 11 of 2020 concerning Job Creation as amended by Law Number 6 of 2023, there have been significant changes in the business licensing system and environmental protection instruments, including the integration of environmental approval into risk-based business licensing as regulated in Articles 22 and 23. In the context of oil palm plantations in Sumatra, these changes in norms have legal implications for the fulfillment of business actors' legal obligations in environmental protection and management. This study aims to analyze the impact of oil palm plantation exploitation in Sumatra from an environmental law perspective, particularly in relation to legal violations based on the normative framework of applicable laws and regulations after the enactment of the Job Creation Law.